Malpraktek Farmasi Dalam Prespektif Islam Dan Kemuhammadiyaan - Silmi Kaffah; Oman Fathurohman sw (An-Najat, 2024)
Pharmaceutical malpractice is a serious problem involving inappropriateness or negligence in pharmaceutical care, which can endanger a patient's health. The aim of this research is to analyze and understand the concept of pharmaceutical malpractice from an Islamic and Muhammadiyah perspective. This research method is qualitative, and this type of library research involves collecting and analyzing data from various relevant literature, including books, scientific journals, articles and other documents that discuss malpractice from an Islamic and Muhammadiyah perspective. The results of this study indicate that pharmaceutical malpractice is used to describe medical procedures that are not in accordance with proper procedures, diagnosing patients incorrectly, and administering drugs that do not meet standards. This shows how important the pharmacist profession is and their responsibility to provide services that meet standards. Islam shows its passion for humanizing humans through its flexibility and versatility. It is important for pharmacists to increase professionalism in their pharmacy practice and understand the legal consequences of actions that violate service standards.